The Presence of Simple Renal Cysts Is Associated With Increased Arterial Stiffness in Patients With Abdominal Aortic Aneurysm. (October 2022) - Nishibe, Toshiya; Dardik, Alan; Maekawa, Koki; Kano, Masaki; Akiyama, Shinobu; Nukaga, Saori; Koizumi, Jun; Ogino, Hitoshi
Simple renal cysts (SRC) are associated with the development of abdominal aortic aneurysms (AAA). We hypothesized that patients with AAA and SRC have increased arterial stiffness (AS) compared with patients without SRC . Patients (n=223) with an infrarenal AAA undergoing pulse wave analysis were recruited. Brachial-ankle pulse wave velocity (PWV) was measured (automated oscillometric method) as an index of AS. Participants were categorized into those with increased AS and those with normal/borderline AS (threshold: 1800 cm/s); 134 patients (60.1%) had increased AS and 89 (39.9%) patients had normal/borderline AS. Multivariable analyses showed that age ≥75 years (odds ratio [OR], 2.83; 95% confidence interval [CI], 1.51–5.72; P =.002), systolic blood pressure ≥140 mmHg (OR, 5.05; 95% CI, 2.35–10.83; P <.001), hypertension (OR, 2.28; 95% CI, 1.08–4.79; P =.030), and presence of SRC (OR, 1.89; 95% CI, 1.03–3.46; P =.040) were independent risk factors for increased AS. The presence of SRC is an independent risk factor for increased AS in patients with an AAA. This association suggests that patients with SRC may have severe aortic wall degeneration and thus the presence of SRC may be pathologically linked to the development of AAA.